Bedeutung des FESSH Hand Trauma Komitees in Europa - Battiston, B.; LetiAcciaro, A.; DeLeo, A. (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2013)
In Europe the need for clear definitions of hand surgery facilities regarding trauma is becoming really important to guarantee a correct and up-dated treatment of lesions more and more frequent and complex. The goal for European patients should be to have similar treatment based on appropriate referral and assistance in centres officially accredited for hand surgery. The target for the European countries, giving the correct support to the centres and surgeons treating these problems, should also be to save the costs of residual invalidities. These are some of the reasons for the European Federation of Societies for Surgery of the Hand (FESSH) decided to form a committee (Hand Trauma Committee) devoted to study this problem, trying to give common guidelines and forming an European net of accredited centres. The first step was to collect data through a network of national representatives. Covering a 487 millions population, 309 centres were recorded, including 1 797 surgeons and 20 363 patients treated during January 2006, then having a clear situation of hand trauma treatment through Europe. Next, the HTC worked on 3 definitions: hand trauma, hand trauma surgeons and hand trauma centres and started to accredit centres applying to these well defined criteria. The HTC is now working on scientific consensus on some traumatic lesions but also on the important topic of prevention of hand traumas. This work is expected to improve an homogenous situation throughout Europe focusing on the better use of the given resources for the prevention and the treatment of these traumatic lesions.
Keywords: hand surgery; microsurgery; hand trauma; classification